MEDIA BARU DALAM PEMBANGUNAN PERTANIAN SERTA PROSPEKNYA BAGI GENERASI MILENIAL DI ERA PANDEMI COVID 19 - shinta prastyanti (Jurnal Ilmu Komunikasi Acta Diurna, 2021)
Millennials are synonymous with technology. On the other hand, the prolonged Covid 19 pandemic has many impacts on various sectors including agriculture. Solving that problem requires an alternative solution to make the agricultural sector is still able become a mainstay sector in the midst of this pandemic. The relationship between those aspects is very interesting and important to study. This research using a literature study that is expected to answer the research objectives of how new media can create opportunities and challenges for the agricultural sector to providing new hope for the welfare of farmers, and ability of the millennial generation to seize these opportunities. The study found several interesting points including making agricultural products more economically valuable by utilizing various services offered through new media by packaging and reproducing agricultural products to make them more attractive for potential consumers and utilizing online networks to expand market share. Another result is the millennial generation has adequate capabilities related to this as evidenced by the emergence of young entrepreneurs in the agricultural sector.